Power Generation Enhancement of Horizontal Axis Wind Turbines Using Bioinspired Airfoils: A CFD Study - Hamid R. Kaviani; Mohammad Moshfeghi (Machines, 2023)
This research investigates the performance implications of employing a bioinspired airfoil (seagull’s wing cross-section) in horizontal-axis wind turbines. Specifically, we replaced the S809 airfoil from NREL Phase VI with an airfoil modeled after seagull wings. Initially, we calibrated four coefficients of the GEKO turbulence model for both the S809 and the bioinspired airfoil, utilizing experimental data. Subsequently, using the calibrated generalized k-ω (GEKO) model, we conducted a comparative analysis between the S809 and the seagull airfoils, revealing the considerable superiority of the seagull airfoil in terms of lift and drag coefficients. Furthermore, we numerically simulated the original NREL Phase VI turbine and a modified version where the S809 airfoil was replaced with the seagull airfoil using 3D computational fluid dynamics (CFD) with the airfoil-based-calibrated GEKO turbulence model. This investigation spanned a wide range of air speeds, including 7 m/s, 13 m/s, and 25 m/s. At these wind speeds, we observed a substantial increase in turbine power generation, with enhancements of 47.2%, 204.4%, and 103.9%, respectively. This study underscores the significant influence of nature’s designs in advancing energy extraction within industries, particularly within the wind energy sector.